The Role of Illness Perception and Its Association With Posttraumatic Stress at 3 Months Following Acute Myocardial Infarction - Princip, Mary; Gattlen, Christina; Meister-Langraf, Rebecca E.; Schnyder, Ulrich; Znoj, Hansjörg; Barth, Jürgen; Schmid, Jean-Paul; von Känel, Roland (Frontiers in Psychology, 2018)
Background: The aim of this study was to investigate the relationship between illness perception and posttraumatic stress disorder (PTSD) symptoms at three months following acute myocardial infarction (MI). Methods: Patients (n = 96) were examined within 48 hours and three months after the illness episode. The brief revised illness perception questionnaire (Brief-IPQ) was used to assess patients’ cognitive representation of their MI. At 3-month follow-up, the Posttraumatic Diagnostic Scale (PDS) and the Clinician-Administered PTSD Scale (CAPS) were used to assess the level of PTSD symptoms. Results: The subjective perception of the illness, including higher harmful consequences (r >.35, p < 0.01), higher illness concerns (r >.24, p <0.05) and more emotional impairment (r > .23, p <0.05), was associated with both self-rated and clinician-rated PTSD symptoms. Beliefs regarding harmful consequences after acute MI were independently associated with levels of PTSD symptoms assessed with both the self-rated PDS and CAPS interview (standardized β coefficient = 0.24; P <0.05) adjusted for demographic factors, cognitive depressive symptoms, fear of dying during MI, factors related to study design, and illness severity. Conclusions: The findings suggest that initial perception of acute MI is significantly associated with PTSD symptoms attributable to MI at three months follow-up.